Dissolved organic carbon content and leachability of biomass waste biochar for trace metal (Cd, Cu and Pb) speciation modelling - Mancinelli, Enrico; Baltrėnaitė, Edita; Baltrėnas, Pranas; Marčiulaitienė, Eglė; Passerini, Giorgio (Journal of Environmental Engineering and Landscape Management, 2017)
Dissolved organic carbon (DOC) interacts with dissolved trace metal affecting their mobility and bioavailability through the formation of DOC–metal complexes. Several types of biochar (BC) produced from slow pyrolysis of wood chips (WC), lignin (LG), and digested sewage sludge at 450 and 700 °C were tested for DOC leaching via batch and up-flow percolation test methods. Trace metal (Cd, Cu, and Pb) speciation modelling in BC eluates was carried out combining measured data (i.e., DOC, ph, temperature, and dissolved trace metal concentrations) with data reported in the literature regarding fractions of DOC that are inert or active (i.e., fulvic acids (FA) and humic acids (HA)) in metal binding. BC from LG (BCLG) and WC (BCWC) at 700 °C released lower cumulative amounts of DOC compared with BC at 450 °C in the range 0.02–0.07% and 0.06–0.09% of total carbon content, respectively. For both pyrolysis temperatures, BCWC exhibited a higher tendency to release DOC compared to BCLG. Speciation modelling results showed the predominance of FA and HA complexes of Cd, Cu, and Pb in all the eluates from BCWC and BCLG irrespective of the inert fractions of DOC or the different fractions of active FA and HA considered.